LTR retrotransposon-derived novel lncRNA2 enhances cold tolerance in Moso bamboo by modulating antioxidant activity and photosynthetic efficiency - Zhao, Jiamin; Ding, Yiqian; Ramakrishnan, Muthusamy; Zou, Long-Hai; Chen, Yujing; Zhou, Mingbing (PeerJ, 2025)
In Moso bamboo, the mechanism of long terminal repeat (LTR) retrotransposon-derived long non-coding RNA (TElncRNA) in response to cold stress remains unclear. In this study, several Pe-TElncRNAs were identified from Moso bamboo transcriptome data. qRT-PCR analysis showed that the expression of a novel Pe-TElncRNA2 in Moso bamboo seedlings reached its highest level at 8 hours of cold treatment at 4 °C and was significantly higher in the stems compared to the leaves, roots, and buds. Furthermore, cellular localization analysis revealed that Pe-TElncRNA2 expression was significantly higher in the cytoplasm than in the nucleus. Pe-TElncRNA2 overexpression in Moso bamboo protoplasts showed that Pe-TElncRNA2 positively regulated the expression of FZR2, NOT3, ABCG44 and AGD6 genes. Further validation of this lncRNA in Arabidopsis thaliana enhanced antioxidant activities, as evidenced by increased superoxide dismutase (SOD) activity and proline content, as well as maximum photochemical efficiency PS II in dark-adapted leaves (Fv/Fm), in the transgenic plants compared to the wild-type controls. Conversely, malondialdehyde (MDA) content, a lipid peroxidation marker (a marker of oxidative stress), was significantly reduced in the transgenic plants. Notably, the expression levels of both Pe-TElncRNA2 and the genes that were regulated by this lncRNA were upregulated in the transgenic plants after two days of cold stress treatment. These findings elucidate the critical role of LTR retrotransposon-derived lncRNAs in mediating cold stress responses in Moso bamboo.
Keywords: LTR retrotransposon; Phyllostachys edulis; lncRNA; TElncRNA; Cold stress